Electronic document in civil proceedings - Nowak, Mariusz (Studia Iuridica Toruniensia, 2023)
The article deals with electronic documents and related problems. Electronic evidence is increasingly used in civil cases and its use should be supervised by judges. Also, legal regulations must not lag behind the development of technology and should be appropriately modified and adapted to new technologies. The complexity of electronic data and information and the many problematic issues related to the use of electronic evidence justify the need to look at these issues.